2020
DOI: 10.1061/(asce)wr.1943-5452.0001159
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Direct Policy Search Using Physically Based Operating Rules in Multireservoir Systems

Abstract: This study explores the ways to introduce physical interpretability into the process of optimizing operating rules for multireservoir systems with multiple objectives. Prior studies applied the concept of direct policy search (DPS), in which the release policy is expressed as a set of parameterized functions (e.g., neural networks) that are optimized by simulating the performance of different parameter value combi-nations over a testing period. The problem with this approach is that the operators generally avo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The rules on which dam operators base their release decisions are typically unknown (e.g. Nazemi and Wheater, 2015;Ritter et al, 2020b), usually hindering an adequate representation of the effects of dams in hydrological models. Secondly, large parts of south-east Spain, and in particular the Segura Basin, are situated on a highly karstic topography (Goldscheider et al, 2020), in which hydrologi-cal simulations generally show high uncertainties (Hartmann et al, 2014).…”
Section: Methods Employed For Assessing Compound Flood Impactsmentioning
confidence: 99%
“…The rules on which dam operators base their release decisions are typically unknown (e.g. Nazemi and Wheater, 2015;Ritter et al, 2020b), usually hindering an adequate representation of the effects of dams in hydrological models. Secondly, large parts of south-east Spain, and in particular the Segura Basin, are situated on a highly karstic topography (Goldscheider et al, 2020), in which hydrologi-cal simulations generally show high uncertainties (Hartmann et al, 2014).…”
Section: Methods Employed For Assessing Compound Flood Impactsmentioning
confidence: 99%
“…Giuliani et al (2014) and Giuliani et al (2016) used radial basis networks (RBNs), demonstrating their benefits as universal approximation functions. Likewise, Ritter et al (2020) applied DS using physically based operating models.…”
Section: Introductionmentioning
confidence: 99%
“…Savic et al [7] found that many state-of-the-art (SOTA) optimization techniques in WDS operation optimization involves some kind of metaheuristics. Ritter et al [8] presents a multiobjective direct policy search technique where different heuristic approaches share the individuals of a population among different metaheuristics. This way the different beneficial properties are combined from different metaheuristics but incorrectly chosen hyperprameters of the distinct methods can alter the whole optimization process.…”
Section: Introductionmentioning
confidence: 99%